The value of pimecrolimus in improving quality of life of children with severe eczema — an open non-randomised study - Omolemo Kitchin; Refiloe Masekela; Teshni Moodley; Robin Green (South African Family Practice)
Background: Atopic eczema is a common skin condition. It has the potential to severely impair quality of life in affected children. Pimecrolimus is currently registered for mild-moderate eczema but in clinical practice children with more severe disease are often treated with this therapy in an attempt to find a safe addition to long-term topical corticosteroid usage. The aim of this study was to test the value of pimecrolimus in improving quality of life in children with severe atopic eczema.